2002
DOI: 10.1519/00124278-200211000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Strength Training to Body Image Among a Sample of Female University Students

Abstract: College women enrolled in a strength training class were evaluated before and after the class using a combination of physical fitness measures, including weight, percentage of body fat, body circumference, and strength measures. Fortynine subjects participated in strength training, twice a week for a total of 12 weeks. At the end of the class, participants were asked to respond to 9 open-ended questions dealing with perceptions of body image. Physical results of the study showed a mean weight gain of 1 lb, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
1
5
0
5
Order By: Relevance
“…These results are similar to those from another study (33) , which also showed that there was an improvement in the body image of female college students after a 12-week strength training program. Therefore, evidence shows that the practice of physical exercises and the improvement in some physical fitness components can influence the improvement in body image.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to those from another study (33) , which also showed that there was an improvement in the body image of female college students after a 12-week strength training program. Therefore, evidence shows that the practice of physical exercises and the improvement in some physical fitness components can influence the improvement in body image.…”
Section: Discussionsupporting
confidence: 90%
“…También la práctica deportiva extraescolar se relaciona con mejores puntuaciones en el autoconcepto físico en la mayoría de sus subdominios (a excepción de la imagen corporal que puntúa más alto entre los no practicantes). Este resultado es contrario a otros estudios (Ahmed, Hilton, y Pituch, 2002;Kirkcaldy, Shephard, y Siefen, 2002;Hausenblas y Symons, 2001;Perry et al, 2002) en los que además de fomentar conductas de salud como la práctica de actividad físico-deportiva, aspecto que se relaciona positivamente con el autoconcepto físico, se observa menor presencia en el consumo de alcohol y tabaco. Por el contrario, neumólogos del Departamento de Investigación en Tabaquismo y Enfermedad Pulmonar Obstructiva Crónica del Instituto Nacional de Enfermedades Repiratorias de Méxi-co, aseguran que dicha práctica no influye en la decisión de reducción del hábito de fumar y que no contrarresta sus efectos sino que su combinación potencia riesgos cardiorrespiratorios.…”
Section: Discussionunclassified
“…(40) Resistance training may also potentially reduce the propensity for the development of the female athlete triad and increase self-esteem and body image satisfaction in female athletes. (4, 44) While the use of resistance training in female populations has increased dramatically in the past two decades, an extensive literature search revealed few studies reporting risks involved with resistance training participation in females.…”
Section: Introductionmentioning
confidence: 99%